2016
DOI: 10.1021/acssuschemeng.5b01123
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling of TEMPO Oxidized Cellulose Nanofibrils As Affected by Protonation of Surface Carboxyls and Drying Methods

Abstract: Self-assembling of cellulose nanofibrils (CNFs) as affected by varying extent of protonation on C6 surface carboxyls was investigated under freeze-drying and air-drying processes. Surface carboxyls were protonated from 10.3 to 100%, all on the same TEMPO oxidized and mechanically blended CNFs with identical geometries and level of oxidation. Upon freeze-drying, all CNFs assembled into amphiphilic mass. The mostly charged CNFs assembled into the finest and most uniform fibers (ϕ = 137 nm) that absorbed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 34 publications
6
105
0
Order By: Relevance
“…It is interesting that the 80.8% of the air-dried F4 is close to the air-dried TEMPO oxidized CNFs (80%), although the freeze-dried one is significantly higher (77.9% for F4 vs 66.3% for TEMPO oxidized CNFs). 44 This result further corroborates the hypothesis that induced crystallization is expected to occur during ultrafiltration and air-drying, which seem to supersede the differences in nanocellulose types. Therefore, rapid freezing and freeze-drying of CNFs appear to preserve the crystal structures of nanocellulose and serve better in determining their crystallinity.…”
Section: Acs Sustainable Chemistry and Engineeringsupporting
confidence: 84%
See 1 more Smart Citation
“…It is interesting that the 80.8% of the air-dried F4 is close to the air-dried TEMPO oxidized CNFs (80%), although the freeze-dried one is significantly higher (77.9% for F4 vs 66.3% for TEMPO oxidized CNFs). 44 This result further corroborates the hypothesis that induced crystallization is expected to occur during ultrafiltration and air-drying, which seem to supersede the differences in nanocellulose types. Therefore, rapid freezing and freeze-drying of CNFs appear to preserve the crystal structures of nanocellulose and serve better in determining their crystallinity.…”
Section: Acs Sustainable Chemistry and Engineeringsupporting
confidence: 84%
“…The low thermal stability of freeze-dried CNF could be due to its higher specific surface and much shorter heat diffusion path of the ultrathin fibers, consistent with our previous observation with the TEMPO oxidized CNFs. 44 The XRD spectra of airdried F4 showed cellulose Iβ lattice structure similar to that of the freeze-dried one but higher intensity due to its more compact and smoother structure. The CrI of air-dried F4 was calculated to be 80.8%, slightly higher than the 77.9% of its freeze-dried counterpart.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 82%
“…It has been reported that the NFC aerogel structure formation is directly related to the size and distribution of ice crystals in the frozen state (Aulin, et al 2010). Furthermore, the extent of protonation on the surface carboxyl groups of ANFC produced by TEMPO oxidation affects the aerogel structure (Jiang and Hsieh 2016). High protonation reportedly results in the formation of a porous ultrathin lamellar aerogel structures and high water uptake upon rehydration.…”
Section: Morphology Of Anfc Aerogelsmentioning
confidence: 99%
“…Figure depicts FTIR spectra taken from samples of respective biomasses before and after TEMPO mediated oxidation. The significant absorbance change in the TEMPO treated samples at approximately 1620 cm −1 representing COONa stretching vibration indicates the success of the TEMPO treatment . This peak increases significantly in magnitude for all biomass samples.…”
Section: Resultsmentioning
confidence: 87%